Different Tax Types Effect Equality - Zhang, Yuting (International Journal of Global Economics and Management, 2025)
The passage talks about whether it is much fairer to use income tax or consumption tax for people in different income brackets. We try to explore the history of taxation and both the benefit side and disadvantage side of different types of taxation. I used website, google scholar, having a research of key words like income tax, consumption tax and so on. Look for several essay that fit for my idea and record the data. My conclusion is that instead of consumption by value, further refinement could consider consumption as a portion of income as a better metric. Exemptions should be made readily available for earners in the bottom percentiles. This essay can be used in some situation like some people wanted to find out the tax policy stuff or they want to build a thought about “Perfect tax collection mechanism”. They can have some useful opinion according to my passage.